Profitability Mediation in the Relationship Between Firm Size and Capital Structure with Firm Value: An Empirical Study on Transportation Subsector Companies Listed on the Indonesia Stock Exchange for the 2016–2023 Period - Indah Yuniarti Admarlan; Akhmadi Akhmadi; Intan Purbasari (Journal of Economics, Management, Accounting and Computer Applications, 2026)
This study aims to examine the effect of firm size and capital structure on firm value. Furthermore, profitability is tested as a mediating variable in the relationship between firm size and capital structure with firm value. The population in this study were 38 companies in the Transportation sub-sector listed on the Indonesia Stock Exchange in the 2016-2023 period. Meanwhile, the number of samples in this study was 11 companies, which were determined by purposive sampling technique. Data analysis techniques in this study include descriptive statistics, classical assumption tests, multivariate regression analysis, and hypothesis testing. The results of this study indicate that firm size has a significant negative effect on firm value, contrary to the proposed hypothesis. Capital structure has a significant positive effect on firm value. Firm size has a significant negative effect on profitability, contrary to the proposed hypothesis. Capital structure has a negative and insignificant effect on profitability, contrary to the proposed hypothesis. Profitability has a negative and insignificant effect on firm value. Profitability can mediate the relationship between firm size and firm value. Meanwhile, profitability cannot mediate the relationship between capital structure and firm value.